Development of STEM Workers Based on STEM to Optimize Curriculum 2013 Implementation - Karnuriman, Karnuriman; Haryono, Haryono; Wardani, Sri (Innovative Journal of Curriculum and Educational Technology, 2019)
The success achieved in the learning process is mostly determined by the ability of educators to develop teaching materials for basic automotive technology subjects with essential competencies evaluating battery work. This study aims to develop student worksheets based on Mathematical Science Technology Engaging (STEM), testing their feasibility, validity, and effectiveness. This study uses the Research and Development method and is carried out in the class X light automotive vehicle engineering at Vocational High School Harapan Mulya Kendal. The results of the study were obtained STEM-based student worksheets are appropriate to use so that they provide feedback to students to know the level of success of their learning and Completion in learning outcomes, the validity of STEM-based student worksheets Raising strong motivation and creativity for maximum learning because of guided education. Learning procedural, namely learning directed at the formation of character and work skills of participants, its effectiveness fosters collaboration between students and between students and teachers in the learning process. Based on the results of the development, it shows that the worksheet fulfills valid and practical criteria. It is recommended to be used as an alternative teaching material evaluating the work of the battery. The results of the study have new elements; namely, students know the relevance of concepts, practices, and content that directs thinking scientifically.